Glutathione-Triggered Drug Release from Nanostructures - Latorre, Alfonso; Somoza, Alvaro (Current Topics in Medicinal Chemistry, 2014)
The delivery of drugs can be improved with the use of different carriers, such as those based on nanoparticles. The nanostructures loaded with the therapeutic molecules should be able to reach the target cells and, what is more, release the drugs efficiently. Ideally, the drugs should be delivered only in the target cells, and not along their way to the cells. For these reasons several approaches have been developed to control the release of the drugs at the desired sites. In this review article we have summarized the reports that describe the use of glutathione to trigger the release of the therapeutic molecules from different nanostructures.
Keywords: Glutathione